Law Enforcement and Social Conflict Detection: A Study of Jürgen Moltmann’s Public Theology in the Indonesian Context - Hendy Tan; Iman Kristina Halawa (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
Social conflict in Indonesia is no longer merely incidental but rather systemic and recurrent, rooted in structural inequality, social exclusion, and weak institutional capacity to detect potential conflicts at an early stage. Under these conditions, law enforcementwhich remains legally formalistic and reactivehas not yet been optimized as a mechanism for the early detection of social conflict. Although various studies have examined the relationship between law and conflict, existing approaches tend to be partial and have not been able to integrate legal, moral, and social dimensions simultaneously. This study aims to analyze the limitations of law enforcement in the early detection of social conflict and to reconstruct its function through the perspective of Jürgen Moltmann’s public theology, specifically the concept of the Theology of Hope. This study employs a qualitative approach with a normative-conceptual design within a socio-legal framework through systematic literature review. The findings indicate that the limitations of law enforcement lie in the dominance of a reactive paradigm, a weak orientation toward substantive justice, and the absence of mechanisms sensitive to structural injustice. This study offers an integrative model that positions law as a preventive, responsive, and transformative instrument in the prevention of social conflict, while also providing a theoretical contribution to the development of public theology in the Indonesian context. Abstrak Konflik sosial di Indonesia tidak lagi sekadar bersifat insidental, melainkan sistemik dan berulang, yang berakar pada ketimpangan struktural, eksklusi sosial, dan lemahnya kapasitas institusional dalam mendeteksi potensi konflik sejak dini. Dalam kondisi ini, penegakan hukum yang masih berorientasi legal-formal dan reaktif belum mampu dioptimalkan sebagai mekanisme deteksi dini konflik sosial. Meskipun berbagai studi telah mengkaji hubungan antara hukum dan konflik, pendekatan yang ada cenderung parsial dan belum mampu mengintegrasikan dimensi hukum, moral, dan sosial secara simultan. Penelitian ini bertujuan untuk menganalisis keterbatasan penegakan hukum dalam deteksi dini konflik sosial serta merekonstruksi fungsinya melalui perspektif teologi publik Jürgen Moltmann, khususnya konsep Theology of Hope. Penelitian ini menggunakan pendekatan kualitatif dengan desain normatif-konseptual dalam kerangka socio-legal melalui studi pustaka sistematis. Hasil penelitian menunjukkan bahwa keterbatasan penegakan hukum terletak pada dominasi paradigma reaktif, lemahnya orientasi pada keadilan substantif, serta absennya mekanisme yang sensitif terhadap ketidakadilan struktural. Penelitian ini menawarkan model integratif yang menempatkan hukum sebagai instrumen preventif, responsif, dan transformatif dalam pencegahan konflik sosial, sekaligus memberikan kontribusi teoritis bagi pengembangan teologi publik dalam konteks Indonesia.